Creating the cumulus. (Economist, 2008)
In this article the author examines advances in the design of computer architecture and the development of cloud computing. The term refers to a computer function that will permit users access to significant amounts of data and information without first achieving any specified knowledge or expertise. New software design will allow nonspecialists to perform programming functions.